Management of angular leaf spot of French bean through fungicides - I. YESURAJA, K. RAJAPPAN and (Indian Phytopathology, 2002)
In 1996-97, fungicides (carbendazim, metalaxyl, mancozeb, chlorothalonil, tridemorph, dinocap) and Trichoderma viride were evaluated for their control of Phaeoisariopsis griseola infecting Phaseolus vulgaris in Tamil Nadu, India. Mancozeb gave the best control, followed by tridemorph and carbendazim. T. viride as a seed treatment gave good disease control and improved seed germination.